From Atoms to Cells: Multiscale Modeling of LiNixMnyCozO2Cathodes for Li-Ion Batteries - Morgan L.M.; Islam M.M.; Yang H.; O'Regan K.; Patel A.N.; Ghosh A.; Kendrick E.; Marinescu M.; Offer G.J.; Morgan B.J.; Islam M.S.; Edge J.; Walsh A. (My University, 2025)
First-generation cathodes for commercial lithium-ion batteries are based on layered transition-metal oxides. Research on ternary compounds, such as LiCoO2, evolved into mixed-metal systems, notably Li(Ni,Mn,Co)O2 (NMCs), which allows significant tuning of the physical properties. Despite their widespread application in commercial devices, the fundamental understanding of NMCs is incomplete. Here, we review the latest insights from multiscale modeling, bridging between the redox phenomena that occur at an atomistic level to the transport of ions and electrons across an operating device. We discuss changes in the electronic and vibrational structures through the NMC compositional space and how these link to continuum models of electrochemical charge-discharge cycling. Finally, we outline the remaining challenges for predictive models of high-performance batteries, including capturing the relevant device bottlenecks and chemical degradation processes, such as oxygen evolution. ©